Comparison of Hepatoprotective Activity of Dhatri Lauha (DL) and Dhatri Lauha without Lauha Bhasma (DLWLB) on Carbon Tetrachloride Induced Hepatotoxicity in Wister Rats - Alka Gyanendra Yadav; Piyush Krantikumar Gandhi; Chatragun Eknathrao Lagad; Rajesh Kundlikrao Ingole; Sudhir Raghuttamrao Rajurkar (Journal of Ayurveda)
Introduction:Many herbal drugs are hepatoprotective, but herbs have lesser palatability and require higher doses. The addition of metals like Lauha (iron) may increase palatability and produce quick action within low doses. Hence, the current study will evaluate the hepatoprotective efficacy of Dhatri Lauha (DL) and DL without Lauha Bhasma (LB) (DLWLB) in experimental animals.Methods:Four groups (N = 8) received a single 0.2 ml intraperitoneal injection of carbon tetrachloride (1:1 in liquid paraffin, 9 mg/kg) to induce hepatotoxicity. For 28 days, test group animals were given DL and DLWLB suspended in vehicles at dosages of 45 and 450 mg/kg bd. wt. orally. Silymarin was given orally to the standard control group at a dosage of 100 mg/kg bd. wt. for 28 days. Hepatoprotective effects were analyzed using biochemical parameters such as serum alanine transaminase, serum aspartate transaminase, serum alkaline phosphatase, serum bilirubin, and histopathological studies of the liver.Results:Silymarin and the test drug-treated group showed an increased value of biochemical parameters on the 14th day, and significant decreases were observed on day 28th. These indicate the positive effect of test drugs.Conclusion:Hepatoprotective activity of DL and DLWLB is comparable to that of the conventional medication silymarin. LB addition to the herbal ingredient of DL reduces the dose of herbal ingredients without affecting hepatoprotective activity.